Application of Molecular-Based Research for Identification of Polymorphism Genetics in Animal - Hartatik, Tety
Genetic variations on animal can be identified using several methods base on molecular marker such as PCR-RFLP, sequensing with spesific primer and genotyping with microsatellite maker. We tried to identified the polymorphism genetics on domestic cattle of Indonesia. PCR-RFLP in the part of mitochondrial DNA cytochrome b of those cattle showed that there are two type polymorphims in both marker of Hae III and Hinf I restriction enzymes. The most domestic cattle of Indonesia have two cutting site of Hae III and one cutting site of HinfI. Microsatellite analysis showed that the allele size of domestic cattle of Indonesia have a distinct pattern compare with the range of allele size from microsatellite which previousely pulished by FAO and ISAG. Those results support the existence of genetic variations and the unique allele of domestic cattle of Indonesia.